المعاقون بين التهميش والدمج الاجتماعي في الثقافة الشعبية. - خليل سيد أحمد, عبد الحكيم (Changement Social, 2018)
نال مجال الإعاقة إهتمامًا بالغًا فيالسنوات الأخيرة من الدراسات العلمية والإجتماعية ويرجع هذا الإهتمام إلى الإقناع في المجتمعات المختلفة بأن المعوق كغيره من أفراد المجتمع الأسوياء لهم الحق في الحياة ولهم الحق في النمو بأقصى ما تمكنهم منه قدراتهم وطاقتهم، ومن ناحية ثانية فإن إهتمام المجتمعات بفئات المعوقينترتبط بتغير النظرة المجتمعية إلى هؤلاء الأفراد والتحول من إعتبارهم حالة اقتصادية إلى النظر إليهم كجزء من الثروة البشرية مما يحتم تنمية هذه الثروة البشرية والإستفادة منها إلى أقصى حد ممكن.ولاشك أن عملية الدمج الإجتماعي لفئة المعاقين تمثل أحد العوامل الأساسية في تنميةروحالمواطنةلديهمفيمجتمعهم. وتكمن مشكلة هذا البحث في كيفية حل التناقض بين تهميشالشبابالموصوم بالإعاقة ومحاولة إدماجه في نفس الوقت؟ فليست المسألة إذًا في وجود وسائل متطورة مساعدة للشخص ذي الإعاقة على الإندماج وإنما لا بدّ من تجاوز المحيط المعيق للتواصل التفاعلي والذي يمثله الثقافة الشعبية. The field of disability has receivedgreat attention in recentyears of scientific and social studies. This concernis due to the conviction in varioussocietiesthat the disabled, likeothermembers of the normal society, have the right to life and have the right to grow to the fullestextent possible. Are related to changing the societalview of theseindividuals and the transformation frombeing an economic situation to lookingatthem as part of the humanwealth, whichnecessitates the development and utilization of thishumanwealth to the maximum extent possible. There is no doubtthat the social integration of the disabled group is one of the main factors in the development of the spirit of citizenship in theircommunity. The problem of thisresearchis how to solve the contradiction between the marginalization of young people marked by disability and try to integrateitat the same time? It istherefore not a question of sophisticatedmeans of assistance to the personwithdisabilities to integrate, but itisnecessary to overcome the environmentthatimpedes the interactive communication represented by the popular culture.